Morphing Distribution Trees - On the Evolution of Multicast States under Mobility and an Adaptive Routing Scheme for Mobile SSM Sources - Thomas Schmidt and Matthias Wählisch (Telecommunication systems : modeling, analysis, design and management, 2006)
Source Specific Multicast (SSM) promises a wider dissemination of group distribution services than Any Source Multicast, as it relies on simpler routing strategies with reduced demands on the infrastructure. However, SSM is designed for á priori known and changeless addresses of multicast sources and thus withstands any easy extension to mobility. Up until now only few approaches arose from the Internet research community, leaving SSM source mobility as a major open problem. The purpose of this paper is twofold. At first we analyze characteristic properties of multicast shortest path trees evolving under source mobility. Analytically and by stochastic simulations we derive measures on the complexity of SSM routing under source mobility. At second we introduce a straightforward extension to multicast routing for transforming (morphing) source specific delivery trees into optimal trees rooted at a relocated source. All packet forwarding is done free of tunneling. Multicast service disruption and signaling overhead for the algorithms remain close to minimal. Further on we evaluate the proposed scheme using both, analytical estimates and stochastic simulations based on a variety of real-world Internet topology data. Detailed comparisons are drawn to bi-directional tunneling, as well as to proposals on concurrent distribution trees.